PENGATURAN HUKUM PENENTUAN UANG AIR SUSU IBU DALAM PERKAWINAN ADAT TERANG KAMPUNG DI DESA OEMASI KECAMATAN NEKAMESE KABUPATEN KUPANG - Boy Mau, Deny; Pekuwali, Umbu Lily; Tubahelan, Yohanes G (Petitum Law Journal, 2023)
The existence of variations in determining the dowry in Terang Kampung traditional marriages in Oemasi Village is one of the socio-cultural issues in Oemasi Village, Nekamese District, Kupang Regency. This research aims were to describe the reasons for providing dowry as part of the traditional marriage system, to explore the basic reasons for determining level of dowry, and to explain the implementation of dowry payments in this community. This research applied empirical legal research methods (Empirical Legal Research) with the population were 226 of all the heads of families in Oemasi Village, and 23 of them were selected purposively as sample. The informants in this research were 5 people consisting of the village head, the head of hamlet, village representative body and local traditional elders. Data were analyzed using quantitative and qualitative descriptive methods. The research results indicated that the reason the practice of giving dowry is still implemented in Oemasi Village is because it is part of cultural preservation and respect for parents. The basic principles for determining the price of the dowry are first, the marriage history of the prospective bride's biological mother, the cost of conducting the party as well as the education and employment level of the prospective bride. Furthermore, the traditional marriage system in Oemasi Village consists of 3 stages, namely the first stage is called Lipa Oko or Oko Lipa (Introduction or recognition stages) the second stage is called Puah Manus (Hallf of dowry) and the third stage is called Noni Bijael (Full of dowry). However, not all respondents have completed the three stages of traditional marriage with the main reason is related to economic factors. Therefore, this research recommends that there is a need for deliberation at the village level to find a proper solution regarding the problem of variations in the amount of dowry in Terang Kampung Village Traditional Marriages in Oemasi Village.